Risk factors and treatment for steroid‐related mood and behavior symptoms in preschool children with leukemia: A case series. Issue 2 (12th September 2016) - Samsel, Chase; Muriel, Anna C.
Abstract: Treatment of pediatric acute lymphoblastic leukemia (ALL) relies on systemic corticosteroids for remission; however, they can cause significant mood and behavior changes that interfere with quality of life and may increase risk for injury. This case series reports on preschool children with preexisting developmental and psychiatric risk factors who presented with behavioral side effects that required intervention. Identification of these vulnerable children may provide opportunities for early intervention, anticipatory guidance, and effective treatment to minimize behavioral side effects and improve quality of life and safety during ALL treatment.